2013
DOI: 10.1126/science.1239552
|View full text |Cite
|
Sign up to set email alerts
|

Dosage Compensation via Transposable Element Mediated Rewiring of a Regulatory Network

Abstract: Transposable elements (TEs) may contribute to evolutionary innovations through the rewiring of networks by supplying ready-to-use cis regulatory elements. Genes on the Drosophila X chromosome are coordinately regulated by the Male Specific Lethal (MSL) complex to achieve dosage compensation in males. We show that the acquisition of dozens of MSL binding sites on evolutionarily new X chromosomes was facilitated by the independent co-option of a mutant helitron TE that attracts the MSL complex (i.e. TE domestica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 49 publications
5
187
1
2
Order By: Relevance
“…1B). Previous studies have found that newly evolved sex chromosomes can rapidly acquire DCC-binding sites through amplification of simple GA dinucleotide repeats that approximate the MSL recognition element (MRE) or domestication of MRE-bearing transposable elements Ellison and Bachtrog 2013;Zhou et al 2013).…”
Section: Rox Orthologs Bind the X Chromosomementioning
confidence: 99%
“…1B). Previous studies have found that newly evolved sex chromosomes can rapidly acquire DCC-binding sites through amplification of simple GA dinucleotide repeats that approximate the MSL recognition element (MRE) or domestication of MRE-bearing transposable elements Ellison and Bachtrog 2013;Zhou et al 2013).…”
Section: Rox Orthologs Bind the X Chromosomementioning
confidence: 99%
“…Recently, comparative studies of the mechanism in dosage compensation in Drosophila melanogaster, D. pseudoobscura and D. miranda demonstrated that two waves of TE amplification allowed the evolution of dosage compensation in neo-X-chromosomes (Ellison and Bachtrog, 2013;Chuong and Feschotte, 2013).…”
Section: Transposable Element (Te) Signalsmentioning
confidence: 99%
“…Within the HASs, a GA-rich sequence motif, the MSL recognition element (MRE), is important for MSL-DCC targeting (Alekseyenko et al 2008;Straub et al 2008). Interestingly, in the related species Drosophila miranda, large autosomal fragments have been fused to a proto-X chromosome relatively recently and are apparently on their way to ''catch up'' with dosage compensation by newly acquiring high-affinity MRE sequences from transposon-derived precursor sequences (Alekseyenko et al 2013;Ellison and Bachtrog 2013).…”
mentioning
confidence: 99%